The notion of afterlife in Islam and Sikhism and its implication on muslims and sikhs lives - Ismail, Mohd Hanif; Abdul Jalil, Mohd. Noh (Department of Usul al-Din and Comparative Religion, KIRKHS, IIUM, 2021)
The article deals with the concept of afterlife from the Islamic and Sikhism worldviews. Islam and Sikhism are two religions which promote different belief systems. The former is propagating on absolute monotheistic belief of the One and Only God, while the latter promotes monism, the belief in the reincarnation of God in the Gurus. Despite the differences in the core belief system, both religions addressed similar notion of afterlife in their teachings. Hence, this article explores on the notion afterlife in Islam and Sikhism and its implication on the Muslims and Sikh lives. This research is employing comparative and analysis approaches on relevant texts from Islam and Sikhism to understand further the notion of afterlife in both religions. This article concludes that Islam and Sikhism uphold similar moral values which are shaped by their beliefs in life after this world. Islam and Sikhism promote virtuous way of life in this world by being obedient to God’s commandments in order to live a better life in the next world.